INCORPORATING RECIPROCAL QUESTIONING STRATEGY AND NUMBERED HEADS TOGETHER IN READING CLASS - Ersianawati, NL; Santosa, MH; Suprianti, GAP (Universitas Pendidikan Ganesha, 2018)
This study aimed at investigating the effect of reciprocal questioning strategy combined with numbered heads together on reading comprehension of the eighth grade students in SMP Negeri 2 Singaraja. This study was an experimental study with post â test only control group design. The population of this study was the eighth grade students in SMP Negeri 2 Singaraja in academic year 2017/2018 with the sample of 73 students who were selected by using cluster random sampling. The data were collected using reading comprehension test. The data were analyzed by using independent samples t-test assisted with SPSS 24. The result showed that there was an effect of reciprocal questioning strategy combined with numbered heads together on reading comprehension of the eighth grade students in SMP Negeri 2 Singaraja. The result of independent samples t-test shows that the difference of reading comprehension between reciprocal questioning strategy combined with numbered heads together and reading guide strategy was significant (p